Hip arthroscopy: Indications, outcomes and complications. (June 2018) - Jamil, Mujahid; Dandachli, Wael; Noordin, Shahryar; Witt, Johan
Abstract: Hip arthroscopy has recently occupied an important place in the armamentarium of General Orthopedic and especially hip surgeons. It is an effective and innovative procedure with rapidly expanding indications. Advancements in surgical tools and refinement in techniques has revolutionalized modern Hip arthroscopy. Surgeons are now able to address pathology in and around the hip joint that was either misdiagnosed or poorly understood. The procedure allows detailed visualization of acetabular labrum, femoral and acetabular chondral surfaces, fovea, ligamentum teres, synovium and the extra-articular peri-trochanteric space. Minimally invasive surgery is now performed for diagnoses as well as treatment of a variety of Hip disorders. The acceptance and rates of hip arthroscopy are increasing across the board and the associated literature is expanding every day. Increasing surgical experience and improving technology is contributing for more advanced procedures to become popularized, however long-term outcome data about hip arthroscopy is still relatively sparse. We aim to review hip arthroscopy in the light of recent literature and will discuss the current indications, outcomes and complications of the procedure. Highlights: Hip Arthroscopy. Femoro-acetabular Impingement. Trochanteric pain syndrome.